A taxonomic revision of the genus Linycus Cameron, 1903 from Japan - Kikuchi, Namiki; Konishi, Kazuhiko (Zootaxa, 2021)
The Japanese species of the genus Linycus Cameron are examined with two species recognized. A Holarctic species, L. exhortator (Fabricius) is newly collected from Japan [Hokkaido, Honshû, Shikoku, Kyûshû], and a new species, L. kyoheii sp. nov., is described from Yamanshi Pref., Honshû. The two Japanese species can be distinguished by a white spot on scutellum (present in L. kyoheii vs. absent in L. exhorator), and sculpture of area between gastrocoeli (weakly rugose-punctate in L. kyoheii vs. clearly rugose in L. exhortator). We also compared the Cytochrome c oxidase subunit I (CO1) of Japanese L. exhortator with European L. exhortator. The p-distances between Japanese and European subspecies exhortator were about 2%, whereas between Japanese and Nearctic ssp. thoracius (Cresson) were about 5%. Here we provisionally treat Japanese L. exhorator as nominotypical subspecies. The intra-specific DNA barcode divergence and allopatric color variations are discussed.